Ventricular arrhythmias and athlete's heart. Role of signal-averaged electrocardiography - Biffi, A.; Ansalone, G.; Verdile, L.; Fernando, F.; Caselli, G.; Ammirati, F.; Pelliccia, A.; Santini, M. (European Heart Journal, 1996)
The aim of this study was to assess the prevalence and the prognostic value of ventricular late potentials in apparently healthy top-level athletes with ventricular arrhythmias, and the effect of physiological myocardial hypertrophy (athlete's heart) on the electrogenesis of the signal-averaged electrocardiogram (ECG). Two groups of asymptomatic athletes without underlying heart disease were studied: group A consisted of 35 athletes without arrhythmias and group B of 25 athletes with frequent and complex ventricular arrhythmias (ventricular ectopic beats > 5000.24 h-1 and ventricular couplets > 15.24 h-1). Late potentials were present if athletes had significantly prolonged filtered QRS and low amplitude signal duration and low root mean square voltages at both 25-250 Hz and 40-250 Hz filters. While late potentials were absent in all normal athletes of group A, they were present in seven of 25 (28%) athletes with arrhythmias of group B (P < 0.003). Ten of 25 athletes (five with and five without late potentials) of group B underwent programmed ventricular stimulation using a protocol comprising up to three extrastimuli. No episode of sustained ventricular tachycardia was induced. In four of five athletes with late potentials and in one of five without them, unsustained ventricular responses were induced. Echocardiographically determined left ventricular mass found in both groups of athletes did not influence the pathological result of the signal-averaged ECG parameters. This study shows the applicability of the signal-averaged ECG in identifying ventricular late potentials in a selected population of top-level athletes with frequent and complex ventricular arrhythmias and without overt heart disease; it also shows that the presence of late potentials is not influenced by left ventricular mass, even if extreme ( > 350 g), and it is correlated to a non-sustained ventricular response during an electrophysiological study.